World health crisis: opportunity to think the citizen within the Peruvian neoliberal system - Vigo Castilla, Martha Kruskaya (2021)
The current crisis product of the pandemic has revealed those economic and social problems that continue to be part of the structure of the Peruvian State. Poverty, discrimination, corruption, precarious health services, education and security, state bureaucracy, etc., as well as the large socioeconomic gaps that are reflected in the different conditions with which families are facing the pandemic. The use of the position of power by business elites in our country allows undemocratic practice within the tax system, which favors the most powerful, while harming and punishing the informality in which most of the class finds itself worker of our country. Despite the difficult health situation that is suffered, it is necessary to focus the debate on the condition in which the citizen is within this Peruvian neoliberal paradigm, what are their rights and duties, and try to glimpse how they can deal with a near future post pandemic to try to rewrite history, from homes, work, schools and on the political scene; in order not to repeat old mistakes of the past and present, maintaining the hope of a greater well-being based on democracy and social justice.